Circular Geodetic Number of Certain Graphs - Arul Amirtha Raja, S; Antony Xavier, D (International Journal of Computer Sciences and Engineering, 2025)
A new variant geodetic problem, circular geodetic is defined as follows: Let S=x_1,x_2,...,x_k,x_(k+1)=x_1 be a geodetic set of G. Then S is said to be a circular geodetic set of G, there exists an index i, 1≤i≤k, such that I[x_i,x_(i+1)] contains atleast a vertex v other than x_i and x_(i+1), also I[S]=V(G). The minimum number of vertices needed to form a circular geodetic set is called circular geodetic number of G and it is denoted by g_cir (G).